Enforcement in Spain of an ICSID award. Commentary of the ATSJ Madrid, Civil and Criminal Chamber, of 18 June 2024 - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
In the judgment under review, the Spanish court applies the 1958 New York Convention to a request for exequatur of an ICSID award. In the arbitration proceedings before the Centre, the claimant is an Austrian company - Strabag SE - and the respondent is the State of Libya. The dispute arises out of an investment transaction carried out by the former in the economy of the latter. Libya is not a Contracting State to the Washington Convention and, therefore, the arbitration is brought before ICSID under the Additional Facility Rules. Precisely, this text prevents the Washington Convention from being applied to resolve the request for exequatur of an ICSID award when the arbitration proceedings have been conducted before the Centre under these Rules. This is the reason why the Spanish court applies the New York Convention to the application for exequatur of the ICSID award and also the reason why the court with jurisdiction to hear this application is the High Court of Justice, and not the Court of First Instance, which would have jurisdiction under the Washington Convention.